AB0790 Hyperuricemia in psoriatic arthritis: prevalence and associated factors. (15th June 2017) - Gudu, T; Peltea, A; Balanescu, A; Bojinca, V; Opris, D; Predeteanu, D; Ionescu, R
Abstract : Background: Hyperuricemia is frequent in psoriatic arthritis (PsA) and it seems to be related to metabolic syndrome rather than to extensive psoriatic skin disease [1]. Objectives: The objective of this study was to evaluate the prevalence of hyperuricemia in PsA patients and to identify the associated factors. Methods: Design: cross-sectional study, including consecutive, unselected, adult PsA patients. Data collection: demographic variables (age, gender, disease duration), clinical variables (affected joints, current moderate/severe psoriasis, nail disease, axial involvement, enthesitis, dactylitis), biological factors (acute phase reactants), treatment-related variables (non-steroidal antiinflamatory drugs, corticosteroids, synthetic and biologic disease modifying drugs) and comorbidities [2]. Hyperuricemia was defined as uric acid level above 6.8 mg/dl [3]. Statistical analysis: the factors that were potentially associated with hyperuricemia were assessed by Spearman correlation and uni- and multivariate logistic regressions. Results: In all, 120 PsA patients were included in the study: 69 (57.5%) women, mean age±standard deviation 54±11.8 years, mean disease duration 7±7.4 years; 24 (20%) had moderate/severe psoriasis and 30 (25%) were taking a biologic. A high percentage of patients had cardiovascular comorbidities, i.e., dyslipidemia 80%, hypertension 51.7%, obesity 34.2% and cardiovascular events 34.2%. Around a quarter of patients had hyperuricemia (33; 27.5%). Hyperuricemia was significantly associated with obesity, diabetes, ischemic heart disease and hypertension, but there was no correlation with current skin psoriasis. In the multivariate analysis, it was best explained by diabetes (odds ratio: 4.95, [95% confidence intervals: 1.47; 16.67]), ischemic heart disease (3.61 [1.00; 12.98]) and obesity (1.86 [1.04; 3.32]). Conclusions: Hyperuricemia in PsA is associated with metabolic syndrome rather than skin psoriasis, but further longitudinal studies are needed to identify causal relationships. References: Bruce IN, Schentag CT, Gladman DD. Hyperuricemia in psoriatic arthritis: prevalence and associated features. J Clin Rheumatol 2000;6(1):6–9. Baillet A, Gossec L, Carmona L, et al. Points to consider for reporting, screening for and preventing selected comorbidities in chronic inflammatory rheumatic diseases in daily practice: a EULAR initiative. Ann Rheum Dis 2016;75(6):965–73. Campion EW, Glynn RJ, DeLabry LO. Asymptomatic hyperuricemia. Risks and consequences in the Normative Aging Study. Am J Med 1987;82(3):421–6. Disclosure of Interest: None declared